COMPREHENSIVE ANALYSIS ON BIM LEARNING IN ARCHITECTURE UNDERGRADUATE STUDENTS IN INDONESIA - Wijaya, Elvina Shanggrama; Dharmatanna, Stephanus Wirawan (architecture department, Engineering faculty, Universitas Diponegoro, 2024)
The use of software in architecture has become a necessary skill to effectively communicate designs and coordinate with stakeholders involved in the studio process. Building Information Modelling (BIM) has been integrated into the architectural education curriculum. Designing with BIM can shorten project timelines, thereby maximizing design exploration. This research aims to provide an overview of the BIM learning process in architectural studios. Data was collected through questionnaires distributed to respondents, focusing on architecture students across Indonesia. Additionally, the BIM learning process will be compared with pre-BIM software: the constraints and their influence on student design development are also key focuses of this research, captured through three stages of questionnaires: at the beginning of the semester, mid-semester, and end of the semester. The findings suggest that learning BIM in architectural studios requires adaptation, but is viewed as an important skill for career survival from the students' perspective, thus motivating their learning process.